Double-layer liquid crystal lens array with composited dielectric layer. Issue 2 (26th January 2020) - Li, Rui; Chu, Fan; Dou, Hu; Tian, Li-Lan; Hou, Wen-Yi; Li, Lei; Wang, Qiong-Hua
ABSTRACT: A double-layer liquid crystal (LC) lens array with composited dielectric layer is proposed. In our design, a spatially non-uniform electric field is generated between the strip electrodes, resulting in a gradient refractive index distribution in the LC layer. Since the upper and lower parts of the LC lens array both adopt a composite dielectric layer, the operation voltage of the LC lens array is effectively reduced. In terms of LC lenslet, the double-layer design doubles the phase difference between the centre and the periphery of the LC layer, thereby reducing the focal length of the LC lens array. In addition, the shortest focal length (~1.78 mm) of the LC lens array is obtained at V = 3.3 V, and the LC lens array has a large focusing range. Graphical abstract: uf0001